Who published the name Kalanchoe longiflora (Crassulaceae subfam. Kalanchooideae)? The correct author attribution and typification of this species name - Smith, Gideon F. (Phytotaxa, 2023)
In the literature on Kalanchoe, the name K. longiflora (Crassulaceae subfam. Kalanchooideae), an endemic of the KwaZulu-Natal midlands of South Africa, has been variously attributed to Rudolf Schlechter and/or to John Medley Wood. This matter is reviewed, and it is shown that Schlechter’s contribution to the nomenclature of K. longiflora consisted only of having suggested the name of the species and that it was published by Wood. The typification status of the name K. longiflora is corrected.